Algorithms of electronic digital signature based on algebraic coding - Кузнецов, А.А.; Пушкарев, А.И.; Киян, А.C. (Radiotekhnika, 2017)
The code cryptosystems are considered, the cryptanalysis problem in them is reduced to solving an NP-complex problem of decoding a random linear code. A new scheme of the EDS using algebraic codes is proposed, comparative evaluations of efficiency are carried out for various indicators (stability, complexity of formation and verification of the EDS, volumes of key data, length of signature, etc.).